The diversity and abundance of bacterial and fungal communities in the rhizosphere of Cathaya argyrophylla are affected by soil physicochemical properties - Xie, Peng; Huang, Kerui; Deng, Aihua; Mo, Ping; Xiao, Fen; Wu, Fei; Xiao, Dewei; Wang, Yun (Frontiers in Microbiology, 2023)
Cathaya argyrophylla is an ancient Pinaceae species endemic to China that is listed on the IUCN Red List. Although C. argyrophylla is an ectomycorrhizal plant, the relationship between its rhizospheric soil microbial community and soil properties related to the natural habitat remains unknown. High-throughput sequencing of bacterial 16S rRNA genes and fungal ITS region sequences was used to survey the C. argyrophylla soil community at four natural spatially distributed points in Hunan Province, China, and functional profiles were predicted using PICRUSt2 and FUNGuild. The dominant bacterial phyla included Proteobacteria, Acidobacteria, Actinobacteria, and Chloroflexi, and the dominant genus was Acidothermus. The dominant fungal phyla were Basidiomycota and Ascomycota, while Russula was the dominant genus. Soil properties were the main factors leading to changes in rhizosphere soil bacterial and fungal communities, with nitrogen being the main driver of changes in soil microbial communities. The metabolic capacities of the microbial communities were predicted to identify differences in their functional profiles, including amino acid transport and metabolism, energy production and conversion, and the presence of fungi, including saprotrophs and symbiotrophs. These findings illuminate the soil microbial ecology of C. argyrophylla, and provide a scientific basis for screening rhizosphere microorganisms that are suitable for vegetation restoration and reconstruction for this important threatened species.